Red flags in patients presenting with headache: Clinical indications for neuroimaging - Sobri, M.; Lamont, A.C.; Alias, N.A.; Win, M.N. (The British Institute of Radiology, 2003)
Headache is a very common patient complaint but secondary causes for headache are unusual. Neuroimaging is both expensive and has a low yield in this group. Most patients with intracranial pathology have clinical features that would raise a "red flag". Appropriate selection of patients with headache for neuroimaging to look for secondary causes is very important. Red flags act as screening tools to help in identifying those patients presenting with headache who would benefit from prompt neuroimaging, and may increase the yield. The aim of this study is to evaluate clinical features in patients with headache using neuroimaging as a screening tool for intracranial pathology. 20 red flags were defined. A retrospective study of 111 patients was performed and the outcomes were divided into positive and negative. Abnormal neuroimaging was present in 39 patients. Results were analysed using the Logistic Regression model. Sensitivity and specificity of red flags were analysed to establish the cut-off point to predict abnormal neuroimaging and a receiver operating characteristic (ROC) curve plotted to show the sensitivity of the diagnostic test. Three red flag features proved to be statistically significant with the p-value of less than 0.05 on both univariate and multivariate analysis. These were: paralysis; papilloedema; and "drowsiness, confusion, memory impairment and loss of consciousness". In addition, if three or more red flags from the list were present, this showed strong indication of abnormal neuroimaging, from cut-off point of ROC curve (area under the curve =0.76).